Comparing activity, toxicity and model membrane interactions of Jelleine-I and Trp/Arg analogs: analysis of peptide aggregation - Martins, Danubia Batista [UNESP]; Pacca, Carolina Colombelli; da Silva, Annielle Mendes Brito; de Souza, Bibiana Monson [UNESP]; de Almeida, Margarete Teresa Gottardo; Palma, Mario Sérgio [UNESP]; Arcisio-Miranda, Manoel; dos Santos Cabrera, Marcia Perez [UNESP] (Springer Nature, 2020)
Increasing resistance in antibiotic and chemotherapeutic treatments has been pushing studies of design and evaluation of bioactive peptides. Designing relies on different approaches from minimalist sequences and endogenous peptides modifications to computational libraries. Evaluation relies on microbiological tests. Aiming a deeper understanding, we chose the octapeptide Jelleine-I (JI) for its selective and low toxicity profile, designed small modifications combining the substitutions of Phe by Trp and Lys/His by Arg and tested the antimicrobial and anticancer activity on melanoma cells. Biophysical methods identified environment-dependent modulation of aggregation, but critical aggregation concentrations of JI and analogs in buffer show that peptides start membrane interactions as monomers. The presence of model membranes increases or reduces the partial aggregation of peptides. Compared to JI, analog JIF2WR shows the lowest tendency to aggregation on bacterial model membranes. JI and analogs are lytic to model membranes. Their composition-dependent performance indicates preference for the higher charged anionic bilayers in line with their superior performance toward Staphylococcus aureus and Streptococcus pneumoniae. JIF2WR presented the higher partitioning, higher lytic activity and lower aggregated contents. Despite these increased membranolytic activities, JIF2WR exhibited comparable antimicrobial activity in relation to JI at the expenses of some loss in selectivity. We found that the substitution Phe/Trp (JIF2W) tends to decrease antimicrobial but to increase anticancer activity and aggregation on model membranes and the toxicity toward human cells. However, the concomitant substitution Lys/His by Arg (JIF2WR) modulates some of these tendencies, increasing both the antimicrobial and the anticancer activity while decreasing the aggregation tendency.
Keywords: Aggregation; Antimicrobial and anticancer peptides; Jelleine-I; Peptide–membrane interactions; Short-chain peptides; Zeta potential